Fundusz leśny jako państwowy fundusz celowy - Snarski, Sławomir Jerzy; Martyniuk, Marek (PRAWO i WIĘŹ, 2026)
The aim of the paper is to analyze and evaluate, using the formal-dogmatic method, the applicable legal regulations governing the principles of financial management and the organization of the forest fund in the context of the features that the doctrine of financial law assigns to state appropriated funds. The essence of state appropriated funds is based on linking revenues from precisely defined sources with expenditure on tasks of great social and economic importance. When analyzing the features of the forest fund in terms of the requirements set for state appropriated funds by Article 29 of the Act on Public Finances, it should be stated that despite the fact that the statutory standards do not directly indicate the rank of the forest fund as one of the state appropriated funds, this fund has basic features that determine its belonging to this organizational form of the public finance sector.